A contingent valuation study of marine parks ecotourism: the case of Pulau Payar and Pulau Redang in Malaysia - Yacob, Mohd Rusli; Radam, Alias; Shuib, Ahmad (Canadian Center of Science and Education, 2009)
The present paper has applied dichotomous choice survey design-contingent valuation method (CVM) to investigate empirically the willingness to pay (WTP) of the visitors for ecotourism resources in two selected marine parks in Peninsular Malaysia. Hence, the purpose of this research is to estimate the value of ecotourism resources by using environmental economic tools which focuses on contingent valuation method of WTP. It uses Logit and Probit models to estimate the visitor’s WTP responses for conservation the marine parks for ecotourism. The studies are based on a sample of 215 respondents in Pulau Redang and 153 respondents in Pulau Payar that were randomly interviewed for data collection for both islands in April-July 2007. The results in Pulau Redang indicate that visitors are willing to pay for conservation about RM7.8 and RM10.6 per year for local and international visitors. Meanwhile, in Pulau Payar, the result has shown that local and international visitors are willing to pay about RM7.30 and RM8 respectively. The findings may provide guideline to marine parks and to help develop management policies that enhance ecotourism contribution to sustainable development and conservation in marine parks in Malaysia.